Entrepreneurship : a contemporary approach - Kuratko, Donald F. (Harcourt College Publishers series in entrepreneurship., 2001)
This new edition of Entrepreneurship includes a new section on technology and the emerging trends of e-commerce, and a chapter on women and minority entrepreneurs.